The Relationship Between Disease Severity and Hematologic Parameters in Geriatric Patients with Acute Pancreatitis - Onalan, Erhan; Gökalp, Yusuf; Yakar, Burkay (Progress in Nutrition, 2020)
Background: Acute pancreatitis (AP) is an emergency disease within the field of internal diseases. Its prevalence in the older population has been increasing in parallel to the increase in the older population. Objectives: This study aims to demonstrate the relationship of the platelet/lymphocyte ratio (PLR) and the neutrophil/ lymphocyte ratio (NLR), which were shown to be markers related to systemic inflammation, with Ranson criteria, which indicate the severity of acute pancreatitis at the time of admission, in geriatric (65 years and above) and non-geriatric (age<65 years) patients. Methods: Data from patients with acute pancreatitis who presented to the Internal Medicine Polyclinic at Firat University Medical Faculty Hospital between March 2015- September 2018 were retrospectively evaluated. Results: Platelet/lymphocyte ratio and neutrophil/lymphocyteratio were determined to be positively correlated with CRP, BUN, and WBC among Ranson criteria at the time of admission (respectively; P<0.001; P<0.001; P<0.05). Based on the results of linear regression analysis, we found that neutrophil/lymphocyteratio and platelet/lymphocyte ratio were independent predictors of acute pancreatitis severity. Conclusion: PLR and NLR, which indicate systemic inflammation, can be used as simple and reliable markers to determine acute pancreatitis severity, and can be used more specifically in the geriatric age group.